2001
DOI: 10.1007/s004240100545
|View full text |Cite
|
Sign up to set email alerts
|

The role of dopamine-metabolizing enzymes in the regulation of renal sodium excretion in the rat

Abstract: The intrarenal natriuretic hormone dopamine (DA) is metabolized by catechol-O-methyltransferase (COMT) and monoamine oxidase (MAO). We have previously shown that inhibition of COMT by entacapone results in a potent D1-like receptor-mediated natriuretic response. The present study was performed using anaesthetized rats to compare the importance of MAO and COMT in DA-mediated natriuresis by use of the MAO inhibitor phenelzine. Urinary sodium and DA excretion remained unchanged after MAO inhibition, while excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
2
17
2
Order By: Relevance
“…Since we in the present study have not tested the dependency of the natriuresis on DA receptors, we cannot categorically state that the blunted natriuretic response in COMT gene deleted mice after acute sodium loading is due to the defective DA system. The wild type mice, however, responded with an increased DA activity after sodium loading, as has previously been demonstrated in rats [11-13,16]. The fact that the homozygous and heterozygous mice did not respond with an increased DA activity after sodium loading strongly indicates a renal dopaminergic defect in these animals.…”
Section: Discussionsupporting
confidence: 60%
“…Since we in the present study have not tested the dependency of the natriuresis on DA receptors, we cannot categorically state that the blunted natriuretic response in COMT gene deleted mice after acute sodium loading is due to the defective DA system. The wild type mice, however, responded with an increased DA activity after sodium loading, as has previously been demonstrated in rats [11-13,16]. The fact that the homozygous and heterozygous mice did not respond with an increased DA activity after sodium loading strongly indicates a renal dopaminergic defect in these animals.…”
Section: Discussionsupporting
confidence: 60%
“…Once synthesized, dopamine is transported out of the cell to activate tubular dopamine receptors. The amount of dopamine secreted depends, in part, on the activity of two catecholamine-degrading enzymes, monoamine oxidase (MAO) and catechol-O-methyltransferase (COMT) (18,21,27). Indeed, it has been shown that these enzymes are abundant in tubular cells and their inhibition leads to a significant increase in the availability of renal dopamine.…”
mentioning
confidence: 99%
“…Saline loading may also be associated with decreased renal degradation of dopamine by catechol-o-methyl transferase (COMT) (152) to 3-methoxytyramine (3MT) and eventually to homovanillic acid (HVA). Monoamine oxidase A (MAO-A) is more important than MAO-B (but less important than COMT) in the degradation of renal dopamine to dihydroxyphenyl acetic acid (DOPAC) (210) and eventually to HVA; MAO activity is not altered by sodium loading (151). Salt loading also enhances the egress of synthesized dopamine into the tubular lumen rather than into the interstitial space (215 calcium concentrations are low (Ͻ150 nM) (32).…”
Section: Renal Dopamine Receptorsmentioning
confidence: 99%